Pemanfaatan Sistem E-Budgeting dalam Mitigasi Dampak Inflasi Pada APBD (Pemerintah Kota Medan) - Sari, Wardhani Indah; Fariski, Aditya; Az-zahri, Imam Syahroji; Sukani, M.Aziiz; Sari, Warsani Purnama; Prayudi, Ahmad (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
Inflation is one of the challenges of the economy that has a significant impact on the management of the Regional Budget, including in Medan City. The weakening of people's purchasing power and private fiscal capacity often occurs due to the increase in the price of goods and services. This impact not only leads to regional fiscal accounting, but also to infrastructure development and public services. This study aims to analyze the role of the e-Budgeting system as a tool to mitigate the impact of inflation on the Medan City Regional Budget. The analysis framework uses a quantitative approach with literature study techniques and policy analysis. The results of the study show that e-Budgeting is very effective in increasing the efficiency of budget planning, the accuracy of fund allocation and transparency of regional financial management. This e-Budgeting system will allow the government to make adjustments to priority programs affected by inflation, such as the provision of social assistance and the implementation of infrastructure development. However, its implementation in Medan has been hampered by technical incompetence and the capacity of the apparatus. Therefore, this study recommends strengthening the integration of e-Budgeting with the regional planning system and increasing training for the apparatus to maximize its role in fiscal stabilization. These findings contribute to the literature on regional financial governance and adaptive policies to macroeconomic dynamics.